Use of medium chain fatty acids and a phytocomplex in diets for rabbit does - Meinieri, G.; Masoero, G.; Forneris, G. (Progress in Nutrition, 2013)
Summary In the present work, four diets for lactating female rabbits have been compared: diet C, control diet; diet A, containing a “blend” of medium chain fatty acids (Biotrade S.N.C.); diet P, containing extracts plants oil (Glycine S., Menta P., Malus P., Centaurium U.) (Probiotan®, by Biorama S.A.S.); diet M, diet containing three antibiotics (Colistine, Avylamicine, Tiamuline) used for the prevention of diseases. The 4 diets were administered to 63 female rabbits that had given birth to 452 pups, alive at 3 days post partum. The purpose of this study was to determine the survival rate of suckling rabbits. A highly significant (P: 0.002 ÷ <0.0001) reduction in mortality of pups belonging to female rabbits included in the three treatment groups (A: 16.3%, P: 17.2%, M: 14.8%) compared to puppies belonging to female rabbits included in the control group (C: 35.6%) was observed for the period between 0 and 19 days post partum. It was concluded that the vitality of the suckling rabbits in the period from 3 to 19 days post partum was significantly improved through the use of medium chain fatty acids (MCFAs) and by Probiotan® integration in the diets of their mothers. This study shows that the MCFAs and plant extracts may therefore be considered as alternative remedies to antibiotics, as they are free of side effects and do not induce antibiotic resistance in rabbits. Utilizzo di acidi grassi a media catena e di un fitocomplesso nelle diete per coniglie allattanti Nel presente lavoro, sono state confrontate 4 diete per coniglie in lattazione: dieta di controllo C; dieta A, contenente una "miscela" di acidi grassi a catena media (Biotrade S.N.C); dieta P, contenenti estratti oleosi di piante (Glycine S., Menta P., Malus P., Centaurium U.; Probiotan®, Biorama S.A.S.); dieta medicata M, contenente 3 antibiotici (Colistina, Avylamicina, Tiamulina) usati per la prevenzione delle malattie. Le diete sono state somministrate a 63 femmine di coniglio, le cui nidiate erano composte da 452 cuccioli vivi a distanza di 3 giorni dal parto. Lo scopo di questo studio era di determinare il tasso di sopravvivenza dei conigli neonati. È stata osservata una riduzione altamente significativa (P: 0.002 ÷ <0.0001 della mortalità dei coniglietti nati dalle madri appartenenti ai 3 gruppi trattati (A: 16,3%; P: 17,2%; M: 14,8%) rispetto dei coniglietti nati dalle madri appartenenti al gruppo di controllo (C: 35,6%) nel periodo compreso fra 0 e 19 giorni post partum . La vitalità dei neonati è significativamente migliorata attraverso l’utilizzo di acidi grassi a catena media (MCFAs) e attraverso l’integrazione con Probiotan®, nelle diete delle coniglie allattanti. Questo studio dimostra che gli acidi grassi a media catena e i fitocomplessi, utilizzati a scopo profilattico, possono essere considerati come rimedi alternativi agli antibiotici, poiché sono privi di effetti collaterali e non inducono antibiotico-resistenza.